Ciencia y teoría curricular - Darós, W. R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
The purpose of this study is to pay attention to the structure of scientific thinking as a means to form the curriculum. Therefore an analogic concept of science is analysed in order to be useful to different kinds of knowledge and academic matters. This study implies that science thought begins in everyday's thought perfected. In this way science is a powerful tool to develop the human will and moral conduct of a person. The scientific thought is particularly efficient for a didactic theory to balance the psychological aspect of mind in the students with the logic and objective demands.